2021
DOI: 10.1515/hsz-2021-0261
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin increases mitochondrial proteins (VDAC and SDH) and downmodulates AXL and PIM-1 tyrosine kinase receptors in NRAS melanoma cells

Abstract: Melanoma is a type of skin cancer with low survival rates after it has metastasized. In order to find molecular differences that could represent targets of quercetin in anti-melanoma activity, we have chosen SKMEL-103 and SKMEL-28 melanoma cells and human melanocytes as models. Firstly, we observed that quercetin was able in reducing SKMEL-103 cell viability, but not in SKMEL-28. Besides that, quercetin treatment caused inhibition of AXL in both cell lines, but upregulation of PIM-1 in SKMEL-28 and downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…We also screened the 10th protein, which is related to Parkinson's syndrome insomnia (PDB code: 1Y7V; Premkumar et al, 2005). Through a literature review, we found that reverse docking with the top nine proteins could directly or indirectly cause insomnia (Duan et al, 2021;Long et al, 2020;Miglis et al, 2021;Orhan, 2021;Rocha-Brito et al, 2022;Romo-Nava et al, 2022; Premkumar et al, 2005) can achieve the effect of treating insomnia.…”
Section: Reverse Docking Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also screened the 10th protein, which is related to Parkinson's syndrome insomnia (PDB code: 1Y7V; Premkumar et al, 2005). Through a literature review, we found that reverse docking with the top nine proteins could directly or indirectly cause insomnia (Duan et al, 2021;Long et al, 2020;Miglis et al, 2021;Orhan, 2021;Rocha-Brito et al, 2022;Romo-Nava et al, 2022; Premkumar et al, 2005) can achieve the effect of treating insomnia.…”
Section: Reverse Docking Resultsmentioning
confidence: 99%
“…We also screened the 10th protein, which is related to Parkinson's syndrome insomnia (PDB code: 1Y7V; Premkumar et al., 2005). Through a literature review, we found that reverse docking with the top nine proteins could directly or indirectly cause insomnia (Duan et al., 2021; Long et al., 2020; Miglis et al., 2021; Orhan, 2021; Rocha‐Brito et al., 2022; Romo‐Nava et al., 2022; Su et al., 2021; Wang et al., 2022; Zhai et al., 2021), and relevant cell experiments or animal experiments have shown that quercetin has an impact on these nine proteins (Ceresa & Peterson, 2014; Cianci et al., 2015; Cuevas et al., 2011; Khodarahmi et al., 2019; Pakdel, 2018; Vieira & Saraiva, 2014). Insomnia is the most immediate symptom experienced by patients with Parkinson's syndrome.…”
Section: Resultsmentioning
confidence: 99%